Clinical spectrum and prognostic markers of multi-system inflammatory syndrome in children hospitalised in Northern India - Areesha Alam; Nishant Verma; Shally Awasthi; Dipti Agarwal; Krishna Kumar Yadav; Pradeep Kumar Gupta; Ranjeeta Dadoria; Anita Mehta; Kuldeep Singh; Moinak Sen Sarma; Amita Aggarwal; Banani Poddar; et al. (Clinical Epidemiology and Global Health, 2023)
Background: Multi-system inflammatory syndrome in children (MIS-C) is characterized by hyper-inflammation and multi-organ dysfunction with antecedent SARS-CoV-2 infection. To describe clinical, laboratory characteristics and outcome of children with MIS-C in a low-middle-income-country and to evaluate factors associated with mortality. Methods: Cases (<18 years) fulfilling WHO case-definition of MIS-C from 7 hospitals in Northern-India were included. Clinical, laboratory and treatment variables were compared between survivors and non-survivors using univariate analysis. Logistic regression analysis was performed to identify their independent association with mortality using Model 1: clinical and laboratory parameters and Model 2: clinical, laboratory and treatment parameters. Results: From May to October 2021, 98 children were enrolled with mean age (SD) of 79 months (54.2) and male preponderance (68.4%). Median (IQR) duration to diagnosis was 6 (4–9) days. Clinical features included fever (100%), gastrointestinal manifestations (70.4%), rash (62.2%), non-purulent conjunctivitis (40.8%) and inflammation of oral-mucosa (32.7%) and extremities (31.6%). Shock was noted in 40%, myocardial dysfunction in 39% and coagulopathy in 98.9% of cases. Seventy-five (76.5%) children required ICU admission and 16.3% required Mechanical ventilation (MV). Mortality rate was 18.4%. Logistic regression model 1 identified C - reactive protein (CRP) > 50 mg/L [aOR 9.6 (95% CI 1.8–50.9)] and Prothrombin Time (PT) > 17 seconds at presentation [aOR 13.6 (95% CI 1.6–118.9)] to be independently associated with mortality. Need of MV emerged as independent predictor of mortality on Model 2. Conclusions: Children with MIS-C having high CRP and PT at presentation are at increased odds of dying and require intensive monitoring.